Efektivitas Pengendalian Piutang Usaha dalam Meminimalkan Risiko Piutang Tak Tertagih: Studi Literatur - Ramadanis, Ramadanis; Anita, Putri Ayu; Septiani, Nazila; Sasmita, Silvia Nabila; Putri, Welda Rahma; Ramadhani, Aldiansyah; Diwirya, Ayu Setya (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
In today’s business practices, credit sales have become a key strategy for companies to increase revenue and expand their markets. However, increased credit transactions also increase the risk of bad debts, which can impact a company’s liquidity and financial stability. This study aims to analyze the effectiveness of accounts receivable control in minimizing the risk of bad debts and identifying factors influencing its management. The study employed a qualitative method with a library research approach, reviewing relevant scientific journals, books, and accounting regulations for the 2020–2025 period. Data were analyzed using content analysis techniques to synthesize previous research findings. The study’s findings indicate that the effectiveness of accounts receivable control is influenced by the integration of credit policies, internal controls, accounting information systems, monitoring of accounts receivable aging schedules, and the implementation of the Expected Credit Loss (ECL) approach in accordance with PSAK 109 (formerly PSAK 71). Furthermore, internal and external factors also influence the success of accounts receivable management. This study concludes that integrated and adaptive accounts receivable control plays a role in minimizing the risk of bad debts and maintaining a company’s financial stability.